3D Analysis of Magnetohydrodynamic (MHD) Micropump Performance Using Numerical Method. (15th July 2015) - Derakhshan, S.; Yazdani, K.
Abstract : In the present study, a 3-dimensional model was developed to investigate fluid flow in MHD micro-pumps. Initially, 3D governing equations were derived and numerically solved using the finite volume method/SIMPLE algorithm. The case study was a (MHD) micropump built in the year 2000 (channel length: 20mm, channel width: 800μm, channel height: 380μm and electrode length: 4mm). The applied magnetic flux density was 13mT and the electric current was different for various solutions (10 ~ 140mA). The numerical results were verified by experimental and analytical data for several solutions. In addition effects of magnetic field strength, electric current, geometrical parameters of the MHD micropump, electrode length and electrode location on its performance have been investigated. Finally the results has been considered and discussed.